Ecological Study about Long-Tailed Macaques (Macaca Fascicularis Raffles) As Potential Tourism Spot in Kalisalak, Kebasen, Banyumas, Indonesia - Nasution, Erie Kolya; Rukayah, Siti; Al Hakim, Rosyid Ridlo (International Journal of Scientific Research in Biological Sciences, 2021)
Kalisalak is the name of the sub-district in Kebasen District, Banyumas Regency, Central Java, Indonesia. The region of Kalisalak consisted of plain area and hills region, and one of the villages named Karangbanar Village. This particular village has a religious spot named “Makam Kramat Karangbanar or Mbah Agung Religious Tomb” that has not been developed by the government, it would potentially be a tourism spot so with that being said it needs some development especially when it comes to long-tailed macaques. This study is to comprehend the ecological study of long-tailed macaques within Karangbanar Village. The methodology is through the survey method. To recognize the diversity of plantations, trees, saplings, to analyze those objects with an Important Value Index (IVI). To comprehend the population of long-tailed macaques, through census, and the daily activity, with descriptive analysis. Also, proximate analysis to arrange the feeding quality. The result of environmental factors in Karangbanar Village is covering the temperature, humidity, wind velocity, topography, plant diversity that supports a sustainable life of long-tailed macaques. The result of proximate analysis of leaves as frequently daily food covers the melinjo leaves, sohan-sohan leaves, and nagasari leaves because they highly consisted of protein and fiber.